COST MANAGEMENT ANALYSIS WITH EARNED VALUE METHOD ON ROAD IMPLEMENTATION PROJECT IN UAIACA - QUELECAI TO OSSU BAUCAU CITY, TIMOR LESTE - Alves, Agata Maria Orleans; Tjendani, Hanie Teki; Wulandari, Esti (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Project management plays a critical role in ensuring the success of infrastructure projects like road implementations, which are essential for the development of emerging regions such as Baucau City, Timor Leste. Challenges often arise due to discrepancies between planned schedules and actual implementation, exacerbated by logistical constraints and unforeseen changes in project requirements. Effective cost management, exemplified by methods like Earned Value Management (EVM), becomes crucial in maintaining project feasibility and controlling expenditures. The purpose of this study was to analyze the cost of road implementation projects using the Earned Value Analysis Method. The method used in this study is to use the Earned Value Method with a project duration of 18 months, where the importance of the earned value analysis method is very helpful for the owner and project implementer to more easily analyze the performance of the project being carried out so as to provide benefits for the owner and project implementation. The findings revealed a project cost overrun of $205,483.12, attributed to low labor productivity and inadequate management, resulting in extended project timelines and subsequent delays in follow-up activities.